PENGARUH PERUBAHAN STRUKTUR ORGANISASI TERHADAP TINGGINYA TURN OVER INTENTION - Ganda Subrata; Muh Tamrin (Jurnal Ekonomi dan Bisnis Kontemporer, 2018)
In response to volatile market demand and nickel prices, PT Vale undertook effective and efficient measures. One of the steps taken is to downsize the organizational structure or department of support. The impact of downsizing (removal of some support departments), there are some employees who are still retained or transferred to other departments, consequently some employees lose their job or down grade, lack or excess scope of work. After the implementation of the downsizing policy, it was identified that there were high levels of resigned employees and the willingness of the employees to move (Turn over intention). Based on this, the purpose of this study focuses on the influence of organizational or departmental changes on the high Turn Over intention, using Qualitative research method, Instrument research through in-depth interview (interview guide). Data analysis techniques using Miles and Hubermen model through data reduction phase, data presentation / data analysis after data collection, conclusion and verification phase.Keywords: Structural changes, Turn Over Intention